The adventures of Huck Finn [videorecording (DVD)] - Sommers, Stephen; Wood, Elijah, 1981-; Vance, Courtney B.; Coltrane, Robbie; Robards, Jason; Perlman, Ron, 1950-; Ivey, Dana; Twain, Mark, 1835-1910 (Distributed by Buena Vista Home Entertainment, 2002)
Huck Finn, a 19th-century boy floating down the Mississippi River on a raft with Jim, a runaway slave, becomes involved with a feuding family, two scoundrels pretending to be royalty, and Tom Sawyer's aunt, who mistakes him for Tom.